Implementasi E-Signal Berbasis Pelayanan Digital dalam Mendukung Capaian Target Pajak Kendaraan Bermotor di Kabupaten Sumbawa - Dita Lestari; Reza Muhammad Rizqi (SENTRI: Jurnal Riset Ilmiah, 2026)
This study evaluates the implementation of the E-Signal digital application in supporting motor vehicle tax revenue targets in Sumbawa Regency, a region characterized by expansive geography and infrastructural disparities. The digital transformation of tax services via E-Signal a collaborative innovation by the National Police, Ministry of Home Affairs, and PT Jasa Raharja aims to enhance efficiency, transparency, and accessibility. Employing a qualitative descriptive approach, this research utilizes George C. Edwards III's theoretical framework to analyze policy implementation effectiveness through communication, resources, disposition, and bureaucratic structure. This is integrated with the Technology Acceptance Model (TAM) to investigate user perceptions of usefulness and ease of use. Data were collected through in-depth interviews with key informants from the Police and local revenue office (Samsat/Bappenda), observations, and tax revenue documentation from 2023–2025. Findings reveal that E-Signal has significantly optimized tax revenue by mitigating bureaucratic and geographical barriers, evidenced by increased revenue realization. However, implementation faces technical challenges, including internet instability, server synchronization issues, and administrative hurdles regarding vehicle ownership requirements. The study concludes that while E-Signal serves as a crucial catalyst for reducing tax arrears and reaching high-mobility taxpayers, achieving optimal outcomes necessitates strengthening technological infrastructure, conducting massive socialization, and integrating data synchronization between national and local systems to foster sustainable public trust in digital public services.